Mechanisms of inflammatory microenvironment formation in cardiometabolic diseases: molecular and cellular perspectives - Menghua Liu; Rumeng Chen; Zhiwei Zheng; Shuling Xu; Chunyan Hou; Yining Ding; Mengling Zhang; Meihua Bao; Binsheng He; Sen Li (Frontiers in Cardiovascular Medicine)
Cardiometabolic diseases (CMD) are leading causes of death and disability worldwide, with complex pathophysiological mechanisms in which inflammation plays a crucial role. This review aims to elucidate the molecular and cellular mechanisms within the inflammatory microenvironment of atherosclerosis, hypertension and diabetic cardiomyopathy. In atherosclerosis, oxidized low-density lipoprotein (ox-LDL) and pro-inflammatory cytokines such as Interleukin-6 (IL-6) and Tumor Necrosis Factor-alpha (TNF-α) activate immune cells contributing to foam cell formation and arterial wall thickening. Hypertension involves the activation of the renin-angiotensin system (RAS) alongside oxidative stress-induced endothelial dysfunction and local inflammation mediated by T cells. In diabetic cardiomyopathy, a high-glucose environment leads to the accumulation of advanced glycation end products (AGEs), activating the Receptor for Advanced Glycation Endproducts (RAGE) and triggering inflammatory responses that further damage cardiac and microvascular function. In summary, the inflammatory mechanisms in different types of metabolic cardiovascular diseases are complex and diverse; understanding these mechanisms deeply will aid in developing more effective individualized treatment strategies.